Supply Chain Management Strategy for MSMEs in Reducing Unemployment in Medan City - Muslimatul Husnah Batubara; Siti Aisyah (Journal of Indonesian Management, 2022)
It is impossible to disentangle the contribution of industries and MSMEs present in different parts of Indonesia from the country's rising economic growth. As a result, SMEs confront a variety of challenges, including fiercer competition, trouble accessing finance, underutilized marketing, a lack of superior resources, restricted access to suppliers, the emergence of new rivals, and a lack of preparedness for the unexpected. The supply chain management process takes these issues into account. It is anticipated that micro, small, and medium-sized firms (MSMEs) will play a crucial role in the development of the populace's economy. MSMEs are anticipated to be able to overcome poverty, the traditional development barrier. The goal of this study is to develop a better supply chain management plan that will benefit the residents of Medan, especially MSMEs, and help to lower the unemployment rate. This study uses a qualitative methodology. the collection of data through surveys and the use of website-based supporting materials. As a result, the study's findings show that Medan's unemployment rate has gone up. Many causes, including the rising number of high school graduates who don't pursue higher education, contribute to the rise in the number of unemployed people in the city of Medan. MSMEs thus contribute significantly to lowering the unemployment rate in the city of Medan. The growth of MSMEs is hampered by a number of problems, which prevent them from developing to their full potential. The lack of money, the employment of less labor, and poorly functioning marketing are some of the challenges faced by MSMEs. So in order to lower the unemployment rate, researchers apply a supply chain method.